¿La agricultura familiar ha muerto? Notas preliminares para una genealogía del concepto en el caso argentino. - Caballero, Luis (2025)
This essay aims to provide elements for the construction of a genealogy of the family farming cycle in the Argentine case. The first section characterizes the regional and global context of the emergence of the concept of family farming and we ask whether the cycle of family farming that has been open during the last 30 years has operated - or not - as a tension to the normalization of previous struggles for food sovereignty. The second section presents a first approach to a genealogy of these 30-year cycle of family farming for the Argentine case, proposing an interspersed sequence of periods and milestones that - in the author's opinion - have shaped it. Finally, the third section raises some conclusions and questions that remain open in the face of the current crisis in the family farming cycle.